The proficiency of English communicative skills among homestay staff in Bangli for effective customer service - Geria, Anak Agung Gede Oka; Pastini, Ni Wayan; Lilasari, Luh Nyoman Tri (Yayasan Mitra Persada Nusantara, 2025)
The growth of community-based tourism (CBT) in Indonesia has positioned homestays as a strategic avenue for rural economic empowerment, cultural preservation, and sustainable tourism development. In Bangli, Bali particularly in renowned tourism villages such as Pengelipuran and Undisan—homestays serve as key interfaces between local communities and international visitors. As English functions as the global lingua franca of tourism, oral English communication skills are essential for ensuring high-quality guest experiences. However, many homestay staff possess limited formal English training, raising concerns about their capacity to meet the communicative demands of international tourism. This study aims to assess the oral English communicative competence of Bangli homestay staff using the Common European Framework of Reference for Languages (CEFR) as the evaluative benchmark. Drawing on the theoretical perspectives of communicative competence and integrating insights from tourism communication research, the study adopts a task-based assessment approach to measure performance in practical contexts such as facility descriptions, cultural explanations, and guest interaction scenarios. The findings are expected to provide a nuanced profile of staff competencies across CEFR levels, identify specific linguistic and strategic strengths and weaknesses, and inform targeted training interventions. By aligning language development initiatives with the operational realities of CBT settings, the study seeks to enhance service quality, strengthen cultural exchange, and contribute to the long-term sustainability of homestay programs in rural Bali. This research further adds to the academic discourse on English for Specific Purposes (ESP) in tourism, particularly within developing country contexts.